Characterization and Differentiation of Mycobacterium avium subsp. paratuberculosis from Other Mycobacteria Using Matrix Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry - Ravva, Subbarao V.; Harden, Leslie A.; Sarreal, Chester Z. (Frontiers in Cellular and Infection Microbiology, 2017)
Mycobacterium avium subsp. paratuberculosis (MAP), the causative agent of Johne’s disease in cattle, is responsible for significant economic losses to the U S dairy industry. The pathogen has also been associated with chronic human diseases like Crohn's disease, type 1 diabetes and multiple sclerosis. Determining causation requires rapid characterization and source tracking the pathogen. Here, we used matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry to characterize and differentiate strains of MAP from 14 other species of Mycobacterium from bovine, human and environmental sources. Lysates from cells disrupted by bead beating in TFA-acetonitrile solution were analyzed by MALDI-TOF. MAP strains were differentiated by mass spectral profiles that are distinct from each other and from other Mycobacterium species. Cluster analysis of spectral profiles indicates two distinct clusters, one dominated by the members of avium complex and a second group dominated by members of fortuitum and parafortuitum complexes. We believe that MALDI-TOF methods can be used to differentiate and source-track MAP strains.